Facial Fat Grafting Cannula: A Tool to Facilitate Closed Irrigation in Flexor Tenosynovitis - Lucas Kreutz-Rodrigues, MD; Mehmet Furkan Tunaboylu, MD; Steven L. Moran, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Pyogenic flexor tenosynovitis (PFT), also known as septic or suppurative flexor tenosynovitis, is a closed-space infection of the hand’s flexor tendon sheath that necessitates timely diagnosis and treatment. The treatment consists of antibiotic therapy often combined with prompt surgical treatment. The most common surgical approach is the closed irrigation technique, which involves inserting a 16-gauge angiocatheter in the proximal aspect of the flexor tendon sheath, leaving the distal end of the Brunner incision open during the irrigation process. However, this method has its own challenges, such as catheter bending and kinking, thereby obstructing the fluid irrigation process and prolonging the operative duration. Instead, we propose the use of a rigid plastic facial fat grafting cannula, which is coupled to a 50-mL syringe with 0.9% saline solution. The cannula is placed at the level of the A1 pulley, and irrigation is easily performed. This simplifies this process by maintaining adequate fluid outflow through the flexor tendon sheath.